(untitled) (Journal of Economic Research & Business Administration, 2019)
The article proposes a mathematical model for estimating the probability of bankruptcy of a firm, existing under condition of uncertainty and targeted critical levels of its financial state. The subject of research is a large logistic company, working under risks of the international market. The article aims to examine the problems of a company’s financial strength in the light of a breach in its work under condition of uncertainty and the issue of the irrational usage of its financial resources during a certain period of time. The data is analyzed by applying the process of a resource withdrawal from the resource container with linear trend and perturbations common for such a case. The advantage of this model is that it allows both to conduct the analytical research and to perform the modeling experiments. The data analysis over the period from 2014 to 2018 exposed the company profitability staggers caused by structure and value changes of the financial flows and, as a result, the bankruptcy risk. In this case it is necessary to develop a model, determining the probability of reaching the zero level of profitability using the business activity array data in consideration of the detected risks.